THE IMPACT OF TACTICAL AND STRATEGIC TRANSFORMATION OF UAV TECHNOLOGY ON MODERN WARFARE - Huseynov, Bahruz; Muradov, Samad (Collection of scientific papers «ΛΌГOΣ», 2025)
The nature of modern warfare is increasingly dependent on technology. One of the most striking examples of these developments is the widespread use of unmanned aerial vehicles (UAVs). UAVs are employed in military operations, particularly in strikes conducted without direct confrontation, changing the nature of combat. Initially used for reconnaissance purposes, this technology has gradually become one of the most critical elements of warfare. Today, drones serve not only reconnaissance and surveillance roles but also direct attacks, precision strikes, and minimizing civilian casualties.